Chemotaxonomic Relationship Among Jujube (Ziziphus Mauritiana Lamk.) Cultivars and Some Related Species - Vashishtha, B B; Pareek, O P; Chandrasekharan, Chandrasekharan (Annals of Arid Zone, 2016)
- Â